A Conjunctive Water Management Model for Metro Manila and Laguna Lake Basins - Liongson, Leonardo Q.; Rojas, David S.; Blanco, Jose M. B.; Soriano, Roberto S. (Philippine Engineering Journal, 2021)
This paper presents the objectives and accomplishments of the water resources management modelling project undertaken by NHRC during the period of 1990-1993. Presented in particular are the features of the Manila Model or CUWARM (Conjunctive-Use Water Resources Management Model), consisting of a coupled groundwater hydraulic-subsidence model, and including daily, monthly, and annual surface-water models. Discussed in detail are the equations and solutions of the groundwater model, the pre-calibration runs for models tests, and the computational and input-output features of the developed Manila Model. The results of the calibration runs for Metro Mania are presented. Conclusions and recommendations on both modeling and management aspects are given. (Based on a paper presented in the Regional Workshop on Management Modelling for Conjunctive Water Use, sponsored by IDRC-GRC-UPERDFI-NHRC, held on March 16-17, 1993, at the National Engineering Center, U.P Diliman, Quezon City)